Normative Conflict Between the State Finance Law and the State-Owned Enterprises Law Regarding the Status of Separated State Assets - Marselina, Putu Prisca; Gede Astariyani, Ni Luh (Westscience Press, 2025)
This study aims to examine the contradiction between the legal perspectives in Law No. 17/2003 concerning state finances and Law No. 19/2003 concerning State-Owned Enterprises (BUMN) regarding separate state assets, and to investigate the legal ramifications of these contradictions on the responsibility and transparency of information in BUMN governance. This study employs normative legal research methodology using statute approach, conceptual approach, and analytical approach. Legal materials consist of primary legal materials including relevant laws and regulations, and secondary legal materials from academic literature, legal books, and scientific journal articles. The research findings indicate fundamental legal perspective differences between the two laws regarding separated state assets. The State Finance Law adopts a broad conception that separated state assets remain part of state finance under public law regime, while the SOE Law adopts a strict separation principle where such assets are no longer part of state assets but become SOE assets under corporate accountability system. This normative conflict creates contradiction in terminis that weakens the application of lex specialis derogat legi generali principle. The legal implications include the creation of a dual accountability system that burdens SOE management, confusion regarding transparency standards between corporate and public transparency, and ambiguity in corporate governance authority and responsibilities that generates high regulatory risk for SOE managers.